A Morphophonemic Analysis of Dholuo Nominals - Okwayo, David Owino (JOOUST, 2023)
Dholuo is one of the languages with a highly productive nominal marking system, particularly in plural formation. Despite this, previous studies have differed sharply on exactly how number is expressed in Dholuo nouns. Previous attempts that have proposed the use of voice polarity, switch alpha rule, the use of articulators or prosodic features in explaining number in Dholuo have been challenged. Moreover, these approaches posit feature polarity (voice, manner or prosodic) as a feature that solely applies t o nouns. However, this feature also occurs in other nominals such as the possessive, adjectives, numerals, genitives and determiners. Again, none of the attempts has endeavored to fully account for the morphemes –e, -i and –ni occurring at the end of Dholuo plural forms. In this regard, this study looked at the whole spectrum of Dholuo nominal morphology comprising of nouns, adjectives, personal pronouns, genitives, interrogatives and demonstratives in an attempt to help characterize further the feature of number in Dholuo. The objectives of the study were: first, to describe the structure of Dholuo nominals; second, to determine how number is realised in Dholuo nouns; and lastly, to explain the morphophonological alternations in Dholuo nominal structure. The study used the theoretical framework known as Optimality Theory (OT). From the accessible population of the 31,573 native speakers of Dholuo in Bondo Town, a sample of 30 respondents was chosen through a systematic random sampling technique. Data for analysis was collected through the targeted elicitation approach using various test frames/matrices administered to this study sample. This study being a descriptive analytical research, the data collected was analysed through interpretive and descriptive process. The analysis shows that the feature “voice,” in general or voice polarity in particular, is not an exclusive constraint for defining Dholuo plurals but is a general descriptive constraint for all Dholuo nominal inflectional processes. The study‟s att empt to account for the morphemes –e, -i and –ni occurring at the end of Dholuo plural forms which were not exhaustively considered by the previous works, established that plural formation in Dholuo is regular and that Dholuo has a basic plural marker –e which has three allomorphic variations –e, -i, -ni occurring in specific, morphophonologically defined environments. The study also found out that phonotactic restrictions in Dholuo nominals play a crucial part in yielding the structures in the plural form s. In particular, articulatory harmony which is the highest ranked constraint defining number in Dholuo nouns, and which provides elaborate and alternative explanation of number in Dholuo to the voice polarity phenomenon defines the alternation in the final syllable of the root. Consonant harmony requires alteration or retention of articulatory parameters so that the behaviour of obstruent, nasal, approximant final noun roots is uniquely defined in each case. Vowel harmony (backness, rounding, height, ATR) is responsible for the morphophonological variations in the vowels in the root in relation to the vowel in the suffix. The suffixation of a morpheme, therefore, has a defining effect on the morphophonology of the nominal constituent in the inflected form. The results of this study are expected to provide new data that offers an alternative description of number in Dholuo nouns, which has been an elusive research question. The findings of the study will be an invaluable pedagogical tool for TOESL as well as being reference material for future studies in Dholuo.
Keywords: Dholuo Nominals